Power hybrid circuit design and manufacture - Taraseiskey, Haim (Electrical engineering and electronics, 1996)
Discusses the fundamental design principles, capabilities, and applications of power hybrid microcircuits and modules--detailing the operation of power semiconductor and passive components, the properties of materials, design guidelines, thermal management, and manufacturing technologies.